1
$\begingroup$

Find the remainder when the polynomial $$1+x^2+x^4+x^6+....+x^{22}$$ is divided by $$1+x+x^2+x^3+...+x^{11}$$

$1+x^2+x^4+x^6+....+x^{22}=\frac{x^{24}-1}{x^2-1}$

$1+x+x^2+x^3+...+x^{11}=\frac{x^{12}-1}{x-1}$

Now$$\frac{1+x^2+x^4+x^6+....+x^{22}}{1+x+x^2+x^3+...+x^{11}}=\frac{x^{12}+1}{x+1}$$

Dont know how to proceed from here

$\endgroup$
  • 2
    $\begingroup$ you are off to a good start. Now just use the standard polynomial division. $\endgroup$ – dezdichado Apr 2 at 4:23
  • $\begingroup$ As @dezdichando said you can use the standard polynomial division, but there is a much better way. Using the Polynomial remainder theorem, you can find an example here or [wikipedia][2] [2]: en.wikipedia.org/wiki/Polynomial_remainder_theorem $\endgroup$ – Baby desta Apr 2 at 4:37
1
$\begingroup$

Assume $\deg Q(x)=11$ and $\deg R(x)\le10$, with \begin{align*} (1+x^2+\cdots+x^{22})=(1+x+\cdots+x^{11})Q(x)+R(x).\tag 1 \end{align*} Multiply $(x^2-1)$ on both sides, \begin{align*} \color{blue}{(x^{12}-1)}(x^{12}+1)&=\color{blue}{(x^{12}-1)}(x+1)Q(x)+(x^2-1)R(x) \end{align*}

implies $\color{blue}{(x^{12}-1)}\mid(x^2-1)R(x)$. Since $\deg (x^2-1)R(x)\le12$, we have \begin{align*} R(x)=k\cdot\frac{x^{12}-1}{x^2-1}=k(1+x^2+\cdots +x^{10}),\qquad k\in\Bbb R. \tag 2 \end{align*} Put $(2)$ into $(1)$ and substitute $x=-1$, $$12=0+k(6)\implies k=2.$$

$$\therefore R(x)=2(1+x^2+\cdots +x^{10}).$$

$\endgroup$
  • 1
    $\begingroup$ We can avoid solving equations by using distributivity - see my answer. $\endgroup$ – Bill Dubuque Apr 2 at 22:50
1
$\begingroup$

Proceeding from where I left off

$$\frac{1+x^2+x^4+x^6+....+x^{22}}{1+x+x^2+x^3+...+x^{11}}=\frac{x^{12}+1}{x+1}$$$$=\frac{x^{12}-1+2}{x+1}=\frac{x^{12}-1}{x+1}+\frac{2}{x+1}=P(x)+\frac{2}{x+1}$$where $P(x)$ is a polynomial since $x^{12}-1$ is divisible by $x+1$.

So $$1+x^2+x^4+x^6+....+x^{22}=P(x)\left(1+x+x^2+x^3+...+x^{11}\right)+\frac{2\left(1+x+x^2+x^3+...+x^{11}\right)}{x+1}$$$$=P(x)\left(1+x+x^2+x^3+...+x^{11}\right)+2\frac{x^{12}-1}{x^2-1}=P(x)\left(1+x+x^2+x^3+...+x^{11}\right)+2Q(x)$$where $Q(x)=1+x^2+x^4+x^6+x^8+x^{10}$

So answer should be $$2\left(1+x^2+x^4+x^6+x^8+x^{10}\right)$$

$\endgroup$
1
$\begingroup$

Upon applying: $\ fg\bmod fh\, =\, f(g\bmod h) =\, $ mod Dstributive Law with $\,z = x^2$

$\begin{align} &\ \,1+\cdots+z^{11}\,\bmod\, (1+\cdots+z^{5})(x+1)\\[.3em] =\ &(1+\cdots+z^{5})\big(1+\color{#c00}{z^6}\,\bmod x+1 \big)\\[.3em] =\ &(1+\cdots+z^{5})\big( 1 + \color{#c00}1\big)\, \ {\rm by}\ \color{#c00}{z^6}\equiv (x^2)^6\equiv \color{#c00}{1},\, \ {\rm by}\ \ x\equiv -1\!\!\!\pmod{\!x+1} \end{align}$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.